Archimetrics: a quantitative tool to predict three‐dimensional meander belt sandbody heterogeneity. (20th April 2016) - van de Lageweg, Wietse I.; van Dijk, Wout M.; Box, Darren; Kleinhans, Maarten G.
Abstract: Fluvial meander belt sediments form some of the most architecturally complex reservoirs in hydrocarbon fields due to multiple scales of heterogeneity inherent in their deposition. Currently, characterization of meander belt bodies largely relies on idealized vertical profiles and a limited number of analogue models that naively infer architecture from active river dimensions. Three‐dimensional architectural data are needed to quantify scales of grain‐size heterogeneity, spatial patterns of sedimentation and bar preservation in a direct relationship with the relevant length scales of active river channels. In this study, three large flume experiments and a numerical model were used to characterize and construct the architecture (referred to as 'archimetrics') and sedimentology of meander belt deposits, while taking reworking and partial preservation into account. Meander belt sandbody width‐to‐thickness ratios between 100 and 200 were observed, which are consistent with reported values of natural meander belts. For the first time, the relief of the base of a meander belt is quantified, enabling improved estimates of connectedness of amalgamated meander belts. A key observation is that the slope and number of lateral‐accretion packages within natural point bar deposits can be well predicted from fairly basic observables, a finding subsequently tested on several natural systems. Probability curves of preserved architectural characteristics for three dimensions were quantified allowing estimates of bar dimensions, baffle and barrier spacing distributions and container dimensions. Based on this, a set of rules were identified for combining reservoir parameters with the identified probability curves on sandbody dimensions and character, to help create more realistic geomodels for estimating exploration success on the basis of seismic and core data. Abstract : We use three large flume experiments and a numerical model to characterize and construct the architecture (referred to as 'archimetrics') and sedimentology of meander‐belt deposits, while taking reworking and partial preservation into account. We quantified probability curves of preserved architectural characteristics for three dimensions allowing estimates of bar dimensions, baffle and barrier spacing distributions and container dimensions. Based on this, we identify a set of rules for combining reservoir parameters with the identified probability curves on sand‐body dimensions and character, to help create more realistic geomodels for estimating exploration success on the basis of seismic and core data.